Clinical significance of blood pressure variability in hypertension - Mazur, E S; Kaliazina, V V (Terapevtic̆eskii arhiv, 1999)
To specify blood pressure (BP) rhythm and variabily at 24-hour monitoring. 24-hour BP monitoring, cardiac echocardiography, measurements of central hemodynamics and vegetative regulation of cardiac rhythm and psychic status were performed in 178 hypertensive subjects. Progression of cardiac function impairment is associated with reduced lowering of night blood pressure and sleep variability, stable BP variability in awake patients. A close negative relationship exists between night BP fall and peripheral resistance, BP night variability and anxiety level. Decreased lowering of night BP seems to reflect morphological changes in the vascular wall, increased variability of wakeful BP reflects less exercise tolerance, that of night BP variability--of growing somatogenically conditioned sympathicotonia and associated anxiety disorders.